Aortic diameters and calcifications in former world-class cyclists - Valenziela, P. L.; Maceira, A.; Santos-Lozano, A.; García-González, M. P.; Higueras Ortega, L.; Díaz-Gonzalez, L.; Boraita, A.; Barranco-Gil, D.; Lucia, A. (Medicine & Science in Sports & Exercise, 2023)
Purpose Concerns on whether athletes--particularly older ones--are at an increased risk of pathological aortic dilation exist, and the prevalence of aortic calcifications in these individuals is unknown. We aimed to compare the dimensions, distensibility, and prevalence of calcifications in the thoracic aorta between former male professional cyclists (cases) and sex/age-matched controls.